Pengaruh Pemasaran Hijau dan Citra Merek terhadap Keputusan Pembelian Produk Aqua : (Studi Kasus: Pada Mahasiswa Manajemen Bisnis Syariah Angkatan 2020 Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sjech M.Djamil Djambek Bukittinggi) - Wirda Damayanti; Amsah Hendri Doni (Transformasi: Journal of Economics and Business Management, 2024)
The intense competitiveness in the commercial sector drives this research. Plastic trash in the environment is causing an increasing amount of natural damage. Customers are becoming more demanding when it comes to eco-friendly items. As a result, companies need to adopt green marketing as a new marketing tactic. Companies can get a competitive edge through green marketing by fostering greater customer trust. Young buyers favor things that are good for the environment. The purpose of this study is to determine the degree to which the purchasing decisions of the Class of 2020 Sharia Business Management students at the Faculty of Economics and Islamic Business, State Islamic University (UIN) Sjech M. Djamil Djambek Bukittinggi, are influenced by green marketing and brand image. Quantitative descriptive research is used in this study. Both primary and secondary data were used. With a sample size of 64 respondents, the study's population consisted of users of AQUA products. Data were gathered by questionnaire distribution and observation. Research instrument tests, which include validity and reliability testing, as well as traditional assumption tests, which include tests for heteroscedasticity, multicollinearity, autocorrelation, and normality, were employed in data processing procedures. using the aid of the SPSS22 program. Based on the research findings, it can be inferred that while brand image has a value of 0.00 less than 0.05 or (0.00<0.05), it can be concluded that brand image partially influences purchasing decisions. This is because the company is implementing a new marketing strategy, namely green marketing. The partially green marketing variable has a value of 0.002 which is smaller than 0.05 or (0.002 <0.05). Businesses can gain a competitive edge by using green marketing to enhance their positive consumer perception. It is possible to conclude that green marketing and brand image jointly have a large influence on purchase decisions because they both simultaneously have a computed F value > F table, or 249,499 > 3,148.